Analysis Of Levels Of Heavy Lead (Pb) in Fishermen’s Urine in Junganyar Coastal Village Based on Passive Smokers and Active Smokers Using Atomic Amborance Spectrophotometer (AAS) Method - Ananda Septiya Putri; Galuh Ratmana Hanum (Universitas Muhammadiyah Sidoarjo, 2023)
The sea is one of the landfills, either directly or by various activities carried out by humans. One of them is dangerous chemicals that are thrown into the sea. Therefore, fishermen are at risk of exposure to these harmful chemicals either directly. In addition, fishermen also have a smoking habit where in cigarettes there are harmful contentsbincluding heavy metals Pb. Lead (Pb) is a heavy metal that is toxic to human health. This study aimsto determine the levels and relationship between ferrous Metals Lead (Pb) in fishermen’s urin in Junganyar Pesisir Village, Socah district, Bangkalan regency based on active smokers and passive smokers. This study is an experimental study with a total sample of 16 fishermen using the Atomic Absorption Spectrophotometer (AAS) Method. The results of the study obtained lead (Pb) also below the threshold of 0,15 mg/L. Pearson 0,05 (0,406) so that H0 was accepted and said there was no relationship between heavy metals and active and passive smokers.